AN ANALYSIS OF USING CODE MIXING FOUND IN INDONESIAN TRANSLATION ORGANIZATION MAGAZINE - I Made Juliarta (Focus Journal : Language Review, 2022)
This study analyzed about the types of code mixing found in the Indonesian Translator organization magazine. The study analyzed about the types and levels of code mixing found in the Indonesian magazine. Intra-sentential code mixing is called as the appearance of a phrase, clause, or a sentence boundary in the utterance of someone. This study applied descriptive qualitative method in analyzing data. Indonesian Translation organization magazine is used as the data source in analyzing data. In collecting data, the researcher applied documentation method. This study applied content analysis that focused on analyzing the types of code mixing defined by Hoffman and the levels of code mixing stated by Suwito. Intra sentential code mixing in the form of word and phrase are found in the data source. It can be seen that there were 7 data of intra sentential code mixing in the form of word found in the data source. Moreover, there were 11 data of intra sentential code mixing in the form of phrases that were found in the data source.